2019
DOI: 10.3389/fmicb.2019.01061
|View full text |Cite
|
Sign up to set email alerts
|

Soybean-Nodulating Strains With Low Intrinsic Competitiveness for Nodulation, Good Symbiotic Performance, and Stress-Tolerance Isolated From Soybean-Cropped Soils in Argentina

Abstract: Soybean is the most important oilseed in the world, cropped in 120–130 million hectares each year. The three most important soybean producers are Argentina, Brazil, and United States, where soybean crops are routinely inoculated with symbiotic N 2 -fixing Bradyrhizobium spp. This extended inoculation gave rise to soybean-nodulating allochthonous populations (SNAPs) that compete against new inoculant for nodulation, thus impairing yield responses. Competitiveness de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 98 publications
2
47
0
Order By: Relevance
“…B. elkanii is another important soybean symbiont that possesses only one flagellar system, similar to the B. diazoefficiens subpolar system. Furthermore, the type strain, B. elkanii USDA 76, moved equally well as B. diazoefficiens USDA 110 in semisolid medium without the addition of a viscous agent (2), and B. elkanii soil isolates were even more motile than B. diazoefficiens or Bradyrhizobium japonicum under these conditions (39), indicating that the single flagellar system of B. elkanii was enough for efficient swimming in such a tortuous environment. However, B. elkanii was unable to swim in viscous medium (2).…”
Section: Resultsmentioning
confidence: 99%
“…B. elkanii is another important soybean symbiont that possesses only one flagellar system, similar to the B. diazoefficiens subpolar system. Furthermore, the type strain, B. elkanii USDA 76, moved equally well as B. diazoefficiens USDA 110 in semisolid medium without the addition of a viscous agent (2), and B. elkanii soil isolates were even more motile than B. diazoefficiens or Bradyrhizobium japonicum under these conditions (39), indicating that the single flagellar system of B. elkanii was enough for efficient swimming in such a tortuous environment. However, B. elkanii was unable to swim in viscous medium (2).…”
Section: Resultsmentioning
confidence: 99%
“…Research in the North and South America showed that the response of inoculation with commercial Bradyrhizobia inoculants differed in soils when soybean was included in previous rotations. This introduced SNB in the soil can either enhance, stay neutral or compete with the elite strain in the commercial inoculants (Thies et al, 1991;Piccinetti et al, 2013;Iturralde et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…HiStick® Soy significantly increased the number and dry weight of nodules on the roots compared the location of the plantation and bacterial strain. Iturralde et al (2019) also obtained a varied number and dry weight of nodules on soybean roots depending on the strain of symbiotic bacteria. This provided the basis for selecting the best one for the production of commercial preparations.…”
Section: Resultsmentioning
confidence: 99%
“…
In soybean cultivation, inoculation of sowing material with bacteria fixing free nitrogen from the air is an especially important procedure (Iturralde et al 2019). This treatment is particularly recommended when native strains of symbiotic bacteria are not present in the soil, or there are too few of them (Zimmer et al 2016).
…”
mentioning
confidence: 99%